1988
DOI: 10.1007/bf02535669
|View full text |Cite
|
Sign up to set email alerts
|

Milk fat globules: Fatty acid composition, size and in vivo regulation of fat liquidity

Abstract: Populations of large and small milk fat globules were isolated and analyzed to determine differences in fatty acid composition. Globule samples were obtained by centrifugation from milks of a herd and of individual animals produced under both pasture and barn feeding. Triacylglycerols of total globule lipids were prepared by thin layer chromatography and analyzed for fatty acid composition by gas chromatography. Using content of the acids in large globules as 100%, small globules contained fewer short-chain ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
110
2
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(122 citation statements)
references
References 22 publications
9
110
2
1
Order By: Relevance
“…The incorporation of unsaturated fatty acids into otherwise palmitic-acid-rich TGs (Fig. 3b,c) would lower the molecular melting temperature and introduce more fluidity to the TG structure [40]. It is evident from the data that a proportion of tripalmitin of 20% or less does not induce beta cell cytotoxicity, whereas if tripalmitin forms greater than 60% of the TG, more than 20% cell death occurs (Figs.…”
Section: Discussionmentioning
confidence: 94%
“…The incorporation of unsaturated fatty acids into otherwise palmitic-acid-rich TGs (Fig. 3b,c) would lower the molecular melting temperature and introduce more fluidity to the TG structure [40]. It is evident from the data that a proportion of tripalmitin of 20% or less does not induce beta cell cytotoxicity, whereas if tripalmitin forms greater than 60% of the TG, more than 20% cell death occurs (Figs.…”
Section: Discussionmentioning
confidence: 94%
“…Pauloin et al (2010) have shown in mouse mammary epithelial cells that UFA modify CLD proliferation and size and protein synthesis. Timmen and Patton (1988) have suggested that the CLD rich in UFA might reach the apical pole of the lactocyte faster than the CLD poor in UFA. In this case, the CLD growth during cell migration would be limited and result in the secretion of smaller MFG.…”
Section: Discussionmentioning
confidence: 99%
“…The SCD catalyzed reaction involves cytochrome b 5 , NAD(P)-cytochrome b 5 reductase and molecular oxygen and the CoA ester of fatty acids as a substrate (Palmquist et al, 2005). Activity of SCD in the ruminant mammary gland is thought to occur as a mechanism to maintain and regulate the fluidity of milk to ensure efficient ejection from the mammary glands (Timmen and Patton, 1988). Stearoyl and palmitoyl-CoA are the preferred substrates for SCD with 18:0 to OA being the predominant precursor:product of SCD in the bovine mammary epithelial cell (bMEC) (Palmquist et al, 2005;Bernard et al, 2008).…”
Section: Mammary Lipogenesismentioning
confidence: 99%
“…It is well established that endogenous synthesis of OA via the action of SCD on 18:0 in the mammary gland is an important point of regulation in milk TAG synthesis and maintenance of milk fat fluidity. In addition to fatty acid chain length, degree of unsaturation and the presence of a cis or trans double bond, the maintenance of milk fat globule fluidity also requires that most fatty acids are esterified at specific positions in milk fat TAG to ensure that milk fat has a melting point at or below 398C (Timmen and Patton, 1988). Under certain conditions, decreases in the availability of 18:0 for endogenous OA synthesis combined with an increase in trans 18:1 at the mammary gland have been proposed as a possible mechanism to explain part of the decrease in milk fat secretion during diet-induced MFD (Loor and Herbein, 2003;.…”
mentioning
confidence: 99%